2019
DOI: 10.1136/emermed-2018-208343
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and determinants of high-risk unscheduled return visits to the emergency department

Abstract: BackgroundHigh-risk unscheduled return visits (HRURVs), defined as return visits within 72 hours that require admission or die in the emergency department (ED) on representation, are a key quality metric in the ED. The objective of this study was to determine the incidence and describe the characteristics and predictors of HRURVs to the ED.MethodsCase–control study, conducted between 1 November 2014 and 31 October 2015. Cases included all HRURVs over the age of 18 that presented to the ED. Controls were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…It is estimated that only 5-10% of return ED visits are associated with potential deficiencies in care. [7][8][9][10] More recent studies have examined patient outcomes after return ED visits as an alternative quality metric, such as hospitalization rates after ED revisits [11][12][13][14][15][16] or even inpatient outcomes during the hospitalization after an ED revisit. 17,18 Hospitalization rates after an ED revisit may also be problematic because ED admission rates per se are highly variable across EDs.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…It is estimated that only 5-10% of return ED visits are associated with potential deficiencies in care. [7][8][9][10] More recent studies have examined patient outcomes after return ED visits as an alternative quality metric, such as hospitalization rates after ED revisits [11][12][13][14][15][16] or even inpatient outcomes during the hospitalization after an ED revisit. 17,18 Hospitalization rates after an ED revisit may also be problematic because ED admission rates per se are highly variable across EDs.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…Prior to the emergence of Covid-19, several studies assessing return admission indicated associations with increasing age, disease severity, ambulance transport, gastrointestinal or infectious disease symptoms, and prolonged time in the ED. [ [23] , [24] , [25] , [26] , [27] ] Many of these previous conclusions also appear to remain significant to 72-h return admission in the setting of Covid-19. Gastrointestinal symptoms predominate, for example, while increasing age, triage acuity, and ED length of stay all remain significant.…”
Section: Discussionmentioning
confidence: 88%
“…Patients with early representation after discharge from the ED are considered clinically high risk for adverse outcomes and misdiagnosis and this is likely to be reflected in patients who contact NHS 111. 41 This finding has been fed back to the telephone triage service provided by YAS and is likely to be applicable to telephone triage in different settings.…”
Section: Discussionmentioning
confidence: 93%